Living in a multicultural society - Shogar, Ibrahim (2020)
This lecture was delivered to final year students of kulliyyah of medicine, IIUM. It discusses the basic matters of living in multicultural society, in increasingly globalizing world. The lecture exposes students to advantage and disadvantages of living in a multicultural society. It discussed, with students, the following questions: 1. As a medical doctor how you understand the phrase “multicultural society”? 2. How the cultural, religious, and ethnic diversities can contribute in creating unity in increasingly globalizing world? 3. What are the guiding principles to create unity in cultural diversity? 4. In which way the Islamic legacy can contribute to establish such principles?